If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(9x + 5) = 2x + -37 Reorder the terms: 3x + -1(5 + 9x) = 2x + -37 3x + (5 * -1 + 9x * -1) = 2x + -37 3x + (-5 + -9x) = 2x + -37 Reorder the terms: -5 + 3x + -9x = 2x + -37 Combine like terms: 3x + -9x = -6x -5 + -6x = 2x + -37 Reorder the terms: -5 + -6x = -37 + 2x Solving -5 + -6x = -37 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + -6x + -2x = -37 + 2x + -2x Combine like terms: -6x + -2x = -8x -5 + -8x = -37 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + -8x = -37 + 0 -5 + -8x = -37 Add '5' to each side of the equation. -5 + 5 + -8x = -37 + 5 Combine like terms: -5 + 5 = 0 0 + -8x = -37 + 5 -8x = -37 + 5 Combine like terms: -37 + 5 = -32 -8x = -32 Divide each side by '-8'. x = 4 Simplifying x = 4
| 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 | | 1.01(1.27)(9-x)=11 | | 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 | | 24=1.5+3 | | 168*0.8=134 | | 110=6b+4b | | (x-5)-3=-28 | | 3(9y-2.6)+7.2=6(8y-0.1) | | -5b^2=-180 |